Positive Darwinian selection within interferon regulatory factor genes of Gymnocypris przewalskii (Cyprinidae) on the Tibetan Plateau. (March 2016) - Tong, Chao; Tian, Fei; Tang, Yongtao; Feng, Chenguang; Guan, Lihong; Zhang, Cunfang; Zhao, Kai
Abstract: Tibetan Plateau (TP) had experienced phased uplift, resulting in inhospitable environment of low temperature, hypoxia and high ultraviolet radiation for Tibetan wildlife. Many organisms can well adapt to TP, it is of ecological and evolutionary interest to untangle how organisms adapt to extreme environment on TP through evolution. Previous studies mainly focused on hypoxia and metabolism related genes, but we know little about the evolutionary history of immune genes in Tibetan wildlife. In this study, we first identified 10 interferon regulatory factor ( IRF ) genes from Tibetan naked carp Gymnocypris przewalskii . Within this gene family, IRF3, IRF5, IRF7 and IRF8 contained positive selection sites. Evidences indicated that positive selection may lead to IRF genes functional alternations, presumably driving genes towards adaptation to the environmental changes. Taken together, our results suggested 4 candidate genes as interesting targets for further experimental confirmation of their functional variations and contributions to high altitude adaptation in Tibet fish. Graphical abstract: Highlights: We cloned and sequenced 10 IRFs from Tibetan naked carp Gymnocypris przewalskii . We found signals of positive selection in 4 IRFs in naked carp. Positive selection may lead the function shift within naked carp IRFs .